Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations SEVENTH GROUP OF LESSONS CLEANLINESS OF PERSONAL CLOTHING SYLLABUS Necessity for cleanliness of clothing. Removal of dust and dirt from coats, etc. — how and where and when to do it. Cleaning of boots. Cleanliness of headgear. Undue number of garments worn involves undue amount of labour in keeping them clean. Need for frequent changes of underwear — for clean shorts, vests, knickers, stockings, etc. Realisation that coloured clothing becomes soiled as quickly as white clothing, though it shows the dirt less. Advantages of drying clothing in sunshine. Value of children wearing everything washable. Avoid woolly tam-o'-shanters. NOTES ON METHOD The habits of personal cleanliness in connection with coats and external clothing may be taught and encouraged in the same way as habits of personal cleanliness in respect of the face and hands, at a very early stage of the child's school career. Very young children will realise that they perspire a great deal as they run about, and that this perspiration makes their clothes damp. The odour of clothes worn for a few days, during which they become damp on the body and subsequently dry, is perceptible on examination. Quite young children can be made to understand that such clothing is dirty, though it does not look dirty. At a later stage children will realise that it is useless 56 177/5/8/3